The Immune System Throws Its Traps: Cells and Their Extracellular Traps in Disease and Protection - Silva, Fátima Conceição (2021)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil.